Persepsi dan Ekspektasi Pembangunan Masyarakat Terhadap Pemerintah Daerah dan Perusahaan Migas - Erwiantono, Erwiantono; Saleha, Qoriah (Makara Human Behavior Studies in Asia, 2012)
Saliki Village, as part of a unique ecosystem of the Mahakam Delta, has various development problems. This region contains oil and gas deposits, which have been mined by multinational companies. This sector has given significant contribution to national income. This area is also covered by mangrove forest that encourages the community to open extensive shrimp ponds. Since 1999, the local government of Kutai Kartanegara has launched a specific development program called Gerbang Dayaku (Gerakan Pengembangan Pemberdayaan Kutai), continued with Gerbang Raja (Gerakan Pembangunan Rakyat Sejahtera). Oil and gas companies operating in the region have also launched various community development programs as their corporate social responsibility. However, the lack of community’s development perceived needs and unestablished prime mover role to hold the community’s economic sustainability have become significant development problems.